Relato e análise da atividade de Extensão Universitária “Produção sustentável de alimentos: você conhece?" - Silvério, Gabriel (Universidade Federal de São Carlos, 2025)
We invited high school students and teachers from schools in the city of Araras for technical visits to the Centro de Ciências Agrárias (CCA) of the Universidade Federal de São Carlos (UFSCar), Araras campus, aiming to stimulate reflections on the roles of public universities, agricultural sciences, and biological conservation in sustainable food production in Brazil within the context of agroecology. These experiences are of utmost importance in seeking a greater connection between the public and the functioning of the university, particularly in the scope of food production, natural resource management and conservation, and the promotion of more equitable social relations. We organized five guided visits to the CCA facilities, all conducted in August 2023. We named this activity: "Sustainable food production: do you know? Open university to high school students". To achieve this, we contacted four public schools in the city of Araras, aiming to engage students in the second and third years of high school (approximately 15 to 17 years old). During the visits, we presented research works on sustainable food production and agroecology conducted by some CCA study groups in an organized and sequential manner, alongside their coordinating professors and undergraduate students who were part of the teams. The activity involved approximately 200 students and teachers across the five visits. During the visit, we collected participants' impressions of the activity on post-it notes, which were later transferred to a digital spreadsheet, which were transformed into word clouds to facilitate the interpretation of these impressions. The results showed that the activity had an impact, but the impressions were still influenced by concepts brought from their individual experiences.
Report and analysis of the University Extension activity “Sustainable food production: do you know?”
Keywords: Ensino médio; Extensão universitária; Ecologia; Produção sustentável; Segurança alimentar; University extension; Ecology; Sustainable production; Food security; High school; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS AGRARIAS::AGRONOMIA